A spatial-temporal analysis of urban growth in melbourne; Were local government areas moving toward compact or sprawl from 2001–2016?. (November 2020) - Rahnama, Mohammad Rahim; Wyatt, Ray; Shaddel, Lia
Abstract: In most cities, urban growth follows a sprawl pattern. In the Melbourne metropolitan area, the Plan Melbourne (2017–2050) was formulated with the aim of reducing sprawl and encouraging sustainable growth. However, the Internet research has shown that in the metropolitan area of Melbourne, no studies aiming to investigate the urban growth using satellite images and analyzing compact urban growth drivers (CUGDs) have been conducted. The objectives of this study of the Melbourne metropolitan area are as follows: 1) Analyzing spatial-temporal changes of normalized difference built-up index (NDBI) 2) Analyzing CUGDs 3) Evaluating the relationship between NDBI and CUGDs. 4) Determining the type of growth in metropolitan area divisions regarding NDBI and CUGDs (2001–2016). To calculate NDBI and urban built-up areas Landsat satellite images were used. Five indicators of population density, separate house density, apartment house density, public transportation usage ratio and distance from the city center were analyzed as CUGDs. The relationship between NDBI and CUGDs was assessed using Ordinary Least Squares (OLS). GIS and ENVI software packages were used for these analyses. The findings revealed that outer Melbourne has experienced the highest rate of change in built-up areas and the direction of developments are toward west, north and south-east in conformity with the government policies. The highest annual rate of change belongs to apartment house density. During 2001–2006, it was 67%, during 2006–2011 45%, during 2011–2016 58%, and during 2001–2016, 61% of the variation in NDBI was explained by the variables. Changes in NDBI under various CUGDs conditions led to the formation of patterns conceptualized at the level of thirty-one local governments (LGs). Based on this study's findings, practical strategies should be formulated to guide the future development of the city and to achieve the Plan Melbourne (2017–2050) objective.